2020
DOI: 10.1186/s12888-020-02615-y
|View full text |Cite
|
Sign up to set email alerts
|

Depression, anxiety, and associated factors in patients with diabetes: evidence from the anxiety, depression, and personality traits in diabetes mellitus (ADAPT-DM) study

Abstract: Background: Depression and anxiety are common psychiatric complications affecting patients with diabetes mellitus. However, data on the prevalence of depression, anxiety, and associated factors among Malaysian diabetic patients is scarce. The Anxiety, Depression, and Personality Traits in Diabetes Mellitus (ADAPT-DM) study aimed to determine the prevalence of depression and anxiety, and their associated factors in the Malaysian diabetic population. Methods: This cross-sectional study recruited 300 diabetic pat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 38 publications
3
17
0
1
Order By: Relevance
“…Chinese adults, which indicated that the prevalence of depression with comorbid anxiety was 19.4% (Gao et al, 2020). The association between higher psychological QoL and lower odds of depression with comorbid anxiety was also well supported by similar ndings reported by other studies of the relationship between psychological QoL and depression and anxiety (Olusina and Ohaeri, 2003;Shumye et al, 2019;Woon et al, 2020).…”
Section: Discussionsupporting
confidence: 80%
“…Chinese adults, which indicated that the prevalence of depression with comorbid anxiety was 19.4% (Gao et al, 2020). The association between higher psychological QoL and lower odds of depression with comorbid anxiety was also well supported by similar ndings reported by other studies of the relationship between psychological QoL and depression and anxiety (Olusina and Ohaeri, 2003;Shumye et al, 2019;Woon et al, 2020).…”
Section: Discussionsupporting
confidence: 80%
“…Generalized anxiety disorder has been found to play a great role as one of the triggers of depression. These data were consistent with studies reporting about a significant overlap between anxiety and depression and that depression-anxiety comorbidity was always common [25][26][27].…”
Section: Discussionsupporting
confidence: 91%
“…Similar results were found in the literature. A number of authors determined that smoking did not affect depression [27,37]. Similarly, according to some studies, family type and smoking status were not involved in developing depression [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…The psychological state of patients requiring corrective surgery is an important factor in good surgical outcome (8). However, because surgery is an invasive treatment, there are many factors influencing the efficacy of surgery, the occurrence of complications, and the recovery time, all of which can affect the psychological reaction of the patient (9).…”
Section: Discussionmentioning
confidence: 99%